Multiple dynamic regimes in colloid‐polymer dispersions: New insight using X‐ray photon correlation spectroscopy. Issue 7 (1st December 2015) - Srivastava, Sunita; Kishore, Suhasini; Narayanan, Suresh; Sandy, Alec R.; Bhatia, Surita R.
ABSTRACT: We present an X‐ray photon correlation spectroscopy (XPCS) study of dynamic transitions in an anisotropic colloid‐polymer dispersion with multiple arrested states. The results provide insight into the mechanism for formation of repulsive glasses, attractive glasses, and networked gels of colloids with weakly adsorbing polymer chains. In the presence of adsorbing polymer chains, we observe three distinct regimes: a state with slow dynamics consisting of finite particles and clusters, for which interparticle interactions are predominantly repulsive; a second dynamic regime occurring above the saturation concentration of added polymer, in which small clusters of nanoparticles form via a short‐range depletion attraction; and a third regime above the overlap concentration in which dynamics of clusters are independent of polymer chain length. The observed complex dynamic state diagram is primarily governed by the structural reorganization of a nanoparticle cluster and polymer chains at the nanoparticle‐polymer surface and in the concentrated medium, which in turn controls the dynamics of the dispersion. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 752–760 Abstract : Colloidal particle and cluster interactions can be tuned by varying polymer properties, such as chain length and concentration. This study uses X‐ray photon correlation spectroscopy to investigate different dynamic regimes in systems containing colloidal disks and weakly adsorbing polymers, and highlights the influence of the dynamics observed in each region on the resulting macroscopic properties of the system.